Contrast effects in response rate and accuracy of delayed matching to sample - Nevin, John A. (2008)
Behavioural contrast is an inverse relation between the response rate in one component of a multiple schedule and the reinforcer rate in an alternated component. To explore possible contrast effects in accuracy as well as response rate, four pigeons were trained in multiple schedules where key pecking produced delayed matching-to-sample trials on a variable-interval schedule. Reinforcer probability for correct matches was constant at .3 in one component, and the conditions of reinforcement were varied in the second component. In Experiment 1, the varied component arranged the same contingencies as the constant component but with reinforcer probabilities of .9 or .1 across conditions. In the varied component, both response rate and accuracy of delayed matching were directly related to reinforcer probability; in the constant component, however, contrast effects on response rate were weak, and there was no evidence of contrast in accuracy of matching. In Experiment 2, the varied component was either variable interval with immediate food reinforcement or extinction. Reliable contrast effects were obtained in both response rate and in accuracy of matching in the constant component, and their magnitudes were correlated within and between subjects. The results of Experiment 2 join previous findings of covariation in the effects of reinforcement on free-operant responding and accuracy of discrimination.